(untitled) (Research, Society and Development, 2022)
Objective: To characterize the epidemiological profile of maternal death cases in the State of Sergipe from 1996 to 2020. Methodology: This is a descriptive, exploratory study with a quantitative approach, which used information from the Mortality Information System. Information on cases of maternal death that occurred in the State of Sergipe between 1996 and 2020 was analyzed. Deaths of women of childbearing age in Sergipe of all age groups, defined as maternal mortality, were considered. Results: During the period analyzed, 580 maternal deaths occurred in women of childbearing age. Of these, there was greater notification in the year 2009 with 36 (6.21%) deaths; the highest rate was identified between 20 and 29 years, with 252 (43.45%); 273 (47.07%) of the deaths were of mixed color/race; 120 (20.69%) of these women had 8 to 11 years of schooling; 274 (47.24%) were single; and 236 (40.69%) died during the puerperium. Conclusion: The characterization of the factors involved in maternal mortality points out that the predominant maternal deaths were in young, brown women. It is evident the need to invest in the strengthening of women’s health care and the implementation of actions or programs directed to this target audience.